Cooperative Problem-Solving Activities for Social Studies, Grades 6-12. - Hickman, Michael (SAGE Publications, 2008)
Featuring current research and new activities, the second edition offers collaborative learning strategies and more than 40 ready-to-use lessons to fully engage students in social studies.